A Contemporary Transport Management System Using Flutter Framework - Dr. V.S. Thiyagarajan; Surendar A; Shahina F; Swetha V; Tamilselvi P (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This project introduces a Flutter-based Transportation Management System (TMS) designed to enhance the efficiency and coordination of student transportation services. The system comprises three distinct modules—Student, Driver, and Admin—each tailored to meet the specific requirements of its users. The student module facilitates user registration and authentication, enabling students to select bus routes based on their current location, track real-time bus positions via Google Maps integration, and access delay reports submitted by drivers. The Driver module allows drivers to register, log in, update trip details including start times and current locations, submit delay reports, and manage student attendance by scanning student ID QR codes. The admin module provides administrators with comprehensive control over the system, allowing them to manage driver and bus information, student records, attendance logs, and delay reports, thereby ensuring effective oversight of transportation logistics. By integrating real-time tracking, QR code-based attendance, and a user-friendly interface, the proposed system aims to streamline transportation operations, enhance communication among stakeholders, and improve overall service reliability.